2021
DOI: 10.1371/journal.pone.0245469
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of infection prevention overlooked in Ethiopia, only one-half of health-care workers had safe practice: A systematic review and meta-analysis

Abstract: Background Effective infection prevention and control measures, such as proper hand hygiene, the use of personal protective equipment, instrument processing, and safe injection practicein the healthcare facilitiesare essential elements of patient safety and lead to optimal patient outcomes. In Ethiopia, findings regarding infection prevention practices among healthcare workers have been highly variable and uncertain. This systematic review and meta-analysis estimates the pooled prevalence of safe infection pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Surgical site, urinary tract and blood stream infections were found to be commonest forms. The type of surgery, patients' underlying medical conditions and the type of the ward were found to be important factors associated with increased risk of HAI in Ethiopia (13,14). Similar results were reported in West Africa and Tanzania where the infection reached over 50% particularly with a high resistant Gram positive and gram negative bacteria (15,16).…”
supporting
confidence: 63%
“…Surgical site, urinary tract and blood stream infections were found to be commonest forms. The type of surgery, patients' underlying medical conditions and the type of the ward were found to be important factors associated with increased risk of HAI in Ethiopia (13,14). Similar results were reported in West Africa and Tanzania where the infection reached over 50% particularly with a high resistant Gram positive and gram negative bacteria (15,16).…”
supporting
confidence: 63%
“…6 Even though HAI is suggested to be reduced by applying standard precautions, the practice among HCWs in clinical settings is low, thus exposing them to risk of infections. 7,8 In Ethiopia, only about half of the HCWs practiced appropriate standard precautions. [9][10][11] The studies identified the associated factors for the poor compliance of the HCWs to the SPs, including lack of infection control programs, lack of training, lack of knowledge and negative attitude towards SPs, inadequate management support, lack of supplies, crowded hospitals and excessive workloads.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous therapy furthermore carries an important risk of fatal healthcare-associated infections [56,57,59,60], as observed in this study. The fact that more than half of the children received intramuscular antipyretics further illustrate the widespread problem of unnecessary and unsafe injection practices in sub-Saharan Africa [61][62][63].…”
Section: Delayed Appropriate Treatment Due To Prehospital Antibiotics...mentioning
confidence: 99%